Ethnobotany of Solieria robusta (Gigartinales, Rhodophyta) in Zamboanga, Philippines - Tito, Oliver; Liao, Lawrence (Science Diliman: A Journal of Pure and Applied Sciences; Vol 12 No 2 (2000), 2007)
A market survey was made at the Zamboanga City public market to determine the diversity of economic macrobenthic algae sold by the local population. Interviews were conducted to obtain information on local names, uses, stock distribution, method of harvest, seasonality, and some aspects of marketing practices.
Keywords: ethnobotany, Solieria robusta, seaweed utilization